(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article analyzes the main components of pedagogical skills, their essence, and their significance in the activities of a pedagogue-physician. It also highlights the relevance of developing pedagogical competencies in the modern medical education system. The role of pedagogical skills in the professional activity of a doctor-teacher, its impact on the quality of education, and the professional formation of students are revealed.